FAMILY FUNCTION AND QUALITY OF LIFE IN ELDERLY IN PALU CITY, INDONESIA - Fauzan,; Sabir, Muhammad; Setyawati, Try; Sridani, Ni Wayan; Devi, Ratna; Nur, Rosmala (International Journal of Psychosocial Rehabilitation, 2020)
To analyze the function of the family towards the quality of life in elderly in Palu City, which is expected to be a basis for the target of a health promotion program on the quality of life in elderly. The research method used an analytic survey of the elderly in the city of Palu. The sample size was 390 respondents. The sample was the 189 elderly victims of natural disaster who lived in the Temporary Shelter (Huntara) and the 201 elderly people who did not live in the Non-Temporary Shelter (Non-Huntara) which conducted in May - June 2019. The research variable was measured by using questionnaires. The characteristics of elderly namely: Age, gender, education, working status, ethnicity, marital status, history of illness, and history of falls. Family function (A = Adaption, P = Partnership, G = Growth, A = Affection, R = Resolve). The quality of life in eldery was measured by using the questionnaires of WHOQOL-BREF. The data analysis used univariate and bivariate analysis with the SPSS application. The results of the study showed that respondents were 53.33% women and 46.67% men, with 47.95% were junior high school graduated and 73.85% were not working. 67.18% elderly were married. Elderly who has a history of illness of 57.69% and history of fall of 36.92%. Mean score of adaption = 1.49, partnership= 1.44, growth = 1.47, affection = 1.29, and resolve = 1.37. Total mean score of APGAR was 7.07. The mean score of physical dimension = 21.7, psychological dimension= 19.9, social relationship dimension = 9, dan environmental dimension = 23.4. The total mean score of quality of life was 74.0. It can be concluded that the family had a good function (score 7.07) for the elderly and the quality of life in elderly was good (score 74.0).